PENGARUH MODEL PEMBELAJARAN MAKE A MATCH PADA MATA PELAJARAN MATEMATIKA DI KELAS IV TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA DI SDN KALIGAWE - Karina Mafaza Sania; Yunita Sari; Rida Fironika Kusumadewi; Nuhyal Ulia (Universitas Islam Sultan Agung, 2025)
Abstract. This study aimed to determine the effect of the Make A Match learning model on fourth-grade students’ critical thinking skills in Matematika at SDN Kaligawe. The Make A Match model is a cooperative learning strategy that engages students in finding matching pairs of question and answer cards, thereby promoting active participation and deeper understanding of the material. This research employed a quantitative approach using a pre-experimental design with pretest and posttest. Data were collected through a critical thinking skills test administered before and after the treatment. The hypothesis testing was conducted using SPSS with the criterion that if Sig. (2-tailed) < 0.05, the hypothesis is accepted. The results showed a significant difference between students’ performance before and after the implementation of the Make A Match model. The SPSS output indicated a significance value of 0.00, which is lower than 0.05, meaning the hypothesis was accepted. The average pretest score was 55, which increased to 80 in the posttest.In conclusion, the implementation of the Make A Match learning model in teaching the Hindu-Buddhist and Islamic kingdoms material in IPAS is more effective than the conventional lecture method in improving fourth-grade students’ critical thinking skills at SDN Kaligawe. Keywords: Make A Match, Critical Thinking